Maylan and his toy top - Lee, Marcy Dans (Adarna House, Inc., 2013)
Maylan found a toy top buried in the sand. Little did he know that this top would cause quite a catastrophe in Langit, Lupa, and Ugsuban, and send Maylan to the horizon.